BIOMATERIALS AS ADDITIVES IN THE SYNTHESIS AND RECYCLING OF SUSTAINABLE ASPHALT ECOBINDERS - Abe, Abraham; Cerra, Carmela; Oliviero Rossi, Cesare; Caputo, Paolino (Università della Calabria, 2023)
In recent years, the course of research has significantly shifted towards the development and testing of eco-friendly practices, products, technologies, policies, initiatives and incentives which are aimed at reducing or even reversing the effects of pollution and several other environmental issues facing the modern society. This approach, in the long run, will also bring about some form of green circular economy where resources are recycled in such a way that the environment is also protected. The use of biomaterials as additives in the production of sustainable asphalt ecobinders is a promising strategy to improve the performance and sustainability of asphalt pavements while safeguarding the environment. Biomaterials such as cellulose, lignin, and chitin, can be derived from renewable sources and have shown potential to enhance the mechanical, rheological, and environmental properties of asphalt mixtures. Materials also derived from waste recycling or blends of bio-based materials and their derivatives also have a huge potential in this regard. This dissertation provides a comprehensive review of bitumen, its structure, the role of additives in asphalt mixes, and the current state of research on the use of biomaterials as additives in sustainable asphalt ecobinders, including their effects on performance and sustainability. The experimental studies carried out in the course of the realization of this body of work revolve around rejuvenation of bitumen obtained from Reclaimed Asphalt Pavement (RAP), the development and use of several bio-based materials (especially from waste) as additives to improve the physico-chemical properties of bituminous mixes and emulsions, conversion of waste materials to substances used for the total or partial replacement of conventional asphalt binders and so on. This body of work also employed the use of innovative practices towards sustainability such as Warm Mix Asphalt (WMA) technology, recycling of RAP, Polymer-modified bitumen (PmB), Bitumen recycling agents and so on. All of this adds up to a significant effort towards a circular economy, resource and environmental conservation, and in general, sustainability. The use of bio-based materials in asphalt industry practices also significantly reduces the health hazards faced by the asphalt workers and the society at large as a result of the mitigation of the issue of greenhouse gas emissions. Several techniques such as Rheology, Scanning Electron Microscopy, Differential Scanning Calorimetry, Nuclear Magnetic Resonance, Infrared Spectroscopy, Atomic Force Microscopy, Light microscopy amongst others were used in the studies carried out in the course of the actualization of this body of work. Some of the results obtained indicate that these biomaterials have huge potential in replacing conventional synthetic additives on an industrial scale and also highlights the need for standardized testing methods and protocols to evaluate the performance and sustainability of these ecobinders. Ultimately, the use of biomaterials as additives in sustainable asphalt ecobinders coupled with recycling of aged bitumen has the potential to reduce the environmental impact of asphalt pavements while maintaining or improving their performance.
UNIVERSITY OF CALABRIA Department of Chemistry and Chemical Technologies PhD in Life Science and Technology. Ciclo XXXV
Keywords: Biopolymers. Bioadditives. Bitumen. Sustainability